Challenges, experience and coping of health professionals in delivering healthcare in an urban slum in India during the first 40 days of COVID-19 crisis: a mixed method study - Leeberk Raja Inbaraj; Carolin Elizabeth George; Shon Rajukutty; Luc P de Witte (BMJ Open)
Objectives To describe the initial dilemmas, mental stress, adaptive measures implemented and how the healthcare team collectively coped while providing healthcare services in a large slum in India, during the COVID-19 pandemic.Setting Community Health Division, Bangalore Baptist Hospital, Bangalore.Study design We used mixed methods research with a quantitative (QUAN) paradigm nested in the primary qualitative (QUAL) design. QUAL methods included ethnography research methods, in-depth interviews and focus group discussions.Participants A healthcare team of doctors, nurses, paramedical and support staff. Out of 87 staff, 42 participated in the QUAL methods and 64 participated in the QUAN survey.Results Being cognizant of the extreme vulnerability of the slums, the health team struggled with conflicting thoughts of self-preservation and their moral obligation to the marginalised section of society. Majority (75%) of the staff experienced fear at some point in time. Distracting themselves with hobbies (20.3%) and spending more time with family (39.1%) were cited as a means of emotional regulation by the participants in the QUAN survey. In the QUAL interviews, fear of death, the guilt of disease transmission to their loved ones, anxiety about probable violence and stigma in the slums and exhaustion emerged as the major themes causing stress among healthcare professionals. With positive cognitive reappraisal, the health team collectively designed and implemented adaptive interventions to ensure continuity of care. They dealt with the new demands by positive reframing, peer support, distancing, information seeking, response efficacy, self-efficacy, existential goal pursuit, value adherence and religious coping.Conclusion The novel threat of the COVID-19 pandemic threw insurmountable challenges potentiating disastrous consequences; slums becoming a threat to themselves, threat to the health providers and a threat for all. Perhaps, a lesson we could learn from this pandemic is to incorporate ‘slum health’ within universal healthcare.